Austrian FDI by main Countries and Industries - Gabor Hunya (FIW - Research Centre International Economics, 2008)
Austria is not among the top global investors, but it is an important regional player in Central and Southeast Europe. Will it keep that position, or will the regional player develop into a global player? This is the question for the future. Based on OeNB data we have found no indication for Austrian FDI expanding outside Europe. We only observe a shift of new FDI within the CEECs to the East and Southeast. As these are fast growing regions, they provide a good opportunity of internationalization for Austrian companies in the next future. Meanwhile, opportunities in even faster growing Asian countries may be missed. Looking at the relationship between FDI growth on one hand and labour productivity, capital productivity and profitability of subsidiaries on the other, we identified the profitability of subsidiaries as the factor most related to the growth of Austrian outward FDI. As a conclusion of the analysis in this paper, policy may have two tasks. One is to encourage companies that are not active internationally to invest abroad. But one can hardly expect that smaller companies go beyond the neighbouring countries. Therefore, another objective could be to support companies to grow beyond SME size because concentrated capital is necessary to enter more remote investment targets. While financial services and some manufacturing industries have internationally active larger companies, other industries may be hindered in their expansion by small firm size and scarcity of knowledge. Especially high-tech industries may need more venture capital and coaching.
Keywords: F21; F23; L21; L25; L60; L80; 330; Austria; FDI; productivity; profitability; economic policy